2012
DOI: 10.1371/journal.ppat.1002610
|View full text |Cite
|
Sign up to set email alerts
|

Induced Release of a Plant-Defense Volatile ‘Deceptively’ Attracts Insect Vectors to Plants Infected with a Bacterial Pathogen

Abstract: Transmission of plant pathogens by insect vectors is a complex biological process involving interactions between the plant, insect, and pathogen. Pathogen-induced plant responses can include changes in volatile and nonvolatile secondary metabolites as well as major plant nutrients. Experiments were conducted to understand how a plant pathogenic bacterium, Candidatus Liberibacter asiaticus (Las), affects host preference behavior of its psyllid ( Diaphorina citri Kuw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
321
1
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(358 citation statements)
references
References 94 publications
21
321
1
15
Order By: Relevance
“…For example, Tomato spotted wilt virus augments the frequency of all feeding behaviors in infected males of its thrips vector (Stafford et al, 2011), and Candidatus Liberibacter asiaticus makes the odor of infected citrus plants initially more attractive for its psyllid vector but then, after virus acquisition, causes psyllids to disperse to non-infected plants (Mann et al, 2012). Similarly, Tomato yellow leaf curl virus enhances the attractiveness of infected tomato plants to virus-free whiteflies (B. tabaci), whereas infected whiteflies lose the capacity to distinguish between infected and healthy host plants (Fang et al, 2013).…”
Section: "Fatal Attraction" When the Host Is A Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tomato spotted wilt virus augments the frequency of all feeding behaviors in infected males of its thrips vector (Stafford et al, 2011), and Candidatus Liberibacter asiaticus makes the odor of infected citrus plants initially more attractive for its psyllid vector but then, after virus acquisition, causes psyllids to disperse to non-infected plants (Mann et al, 2012). Similarly, Tomato yellow leaf curl virus enhances the attractiveness of infected tomato plants to virus-free whiteflies (B. tabaci), whereas infected whiteflies lose the capacity to distinguish between infected and healthy host plants (Fang et al, 2013).…”
Section: "Fatal Attraction" When the Host Is A Plantmentioning
confidence: 99%
“…Indeed, differing persistence times might be a major explanation for the observation that manipulation effects are more frequently reported for intermediate than for final hosts, at least as long as all hosts are animals (Holmes and Bethel, 1972). Plant pathogens, by contrast, require mobile vectors for their dispersal among their immobile final hosts and, therefore, frequently manipulate the quality of their host plant for the vectors (Belliure et al, 2010;Mauck et al, 2010Mauck et al, , 2014aLuan et al, 2013;Shi et al, 2013) as well as the feeding decisions that are taken by their vectors (Stafford et al, 2011;Ingwell et al, 2012;Mann et al, 2012;Fang et al, 2013;Rajabaskar et al, 2014). These changes can be very fine-tuned: for example, plant viruses with a persistent mode of transmission require vectors to feed for a prolonged period of time on infected hosts and, thus, usually tend to improve the quality of the host plants for the vectors.…”
Section: Why Don't All Parasites Manipulate?mentioning
confidence: 99%
“…Mann et al (2012) demonstrated that infected Citrus sinensis plants emitted higher amounts of methyl salicylate, but less methyl anthranilate and Dlimonene than plants not infected by Candidatus Liberibacter asiaticus bacteria. Psyllid bugs (Diaphorina citri) initially chose infected plants but subsequently-after they became carriers of the pathogen-moved to non-infected plants.…”
mentioning
confidence: 99%
“…The most important contributing factors to rapid spread of CLas by ACP are (A) the high dispersal potential of adult psyllids, which is facilitated by their good flight capabilities and small size, enabling them to be blown long distances by wind and go undetected on shipped plants and (B) rapid psyllid population growth, which results from short generation times and the high fecundity of females (Lewis-Rosenblum et al 2015). Additionally, uninfected psyllids are more attracted to CLas-infected trees than to uninfected trees, which may further facilitate rapid pathogen spread (Mann et al 2012). Thus, suppressing ACP populations is important for reducing CLas movement, which in turn maximizes orchard longevity and productivity.…”
mentioning
confidence: 99%